New Carlia fusca complex lizards (Reptilia: Squamata: Scincidae) from New Guinea, Papua-Indonesia - Zug, George R.; Allison, Allen (Zootaxa, 2006)
Recent rapid-assessment surveys in western New Guinea have provided well-documented voucher specimens that show greater speciation within the Carlia fusca complex in this area than indicated by the examination of older museum specimens. Variation in the morphometric and scalation traits of these new species does not differ greatly from other fusca complex species. This result was anticipated owing to the overall low level of variation in these morphological features in the fusca complex. Regionalization of distinct color patterns and abrupt shifts from one pattern to another indicate the existence of a distinct species along much of the southern coast from the Eilanden River basin to Etna Bay and another species from the northern coast of the Bomberai Peninsula. The variation and distribution of fusca complex species are examined for populations in the southern and western “mainland” Papua-Indonesia.